Determinants of Cost of Capital: Kenyan context - kengere, George, Onyiego; Njagi, Manasseh, Mwai; Kamau, Charles Guandaru; Chonga, Luvuno (My University, 2023)
The purpose of this paper was to look at the determinants of the cost of capital for a firm. The study conducted a literature review with the goal of identifying the factors that influence the cost of capital for a firm. The research showed that profitability, liquidity, tax, growth, size, and age of the company are among the major determinants that influence the cost of capital for a firm. Further the research showed a positive correlation between the cost of capital and profitability, liquidity, growth, size, and age of the company. The capital arrangement of a firm is determined on account of the pecking order theory and trade-off theory while bearing in mind the cost elements associated with it. In Kenya, economic stability and political stability are the primary determinants that determine the cost of capital for a firm. This determining factor influences the availability and cost of credit offered by financial institutions in Kenya.
Keywords: Capital Arrangement; Cost of Capital; Leverage; Liquidity; Profitability